Noise Komunikasi dalam Penanganan WABAH COVID-19 (Studi Deskriptif-Kualitatif Penanganan Covid-19 di NTB) - Muhammad Jamiluddin Nur; Pundra Rengga Andhita; Baiq Vira Safitri (Universitas Mataram, 2020)
Muhammad Jamiluddin Nur[1], Pundra Rengga Andhita[2], Baiq Vira Safitri[3]ABSTRACTThis study aims to describe the communication noise that occurs in the process of handling the Covid-19 outbreak in NTB. This research is important to be carried out to provide insight of communication science. In addition, this research can also be a government reference in composing effective communication in handling current and future outbreaks, especially related to communication noise. The method used in this research is descriptive-qualitative. Thus, the data presented is qualitative data. Quantitative data is only used by researchers to strengthen argumentation. Data sources in this research are various mass media, books, research reports that are relevant to this research topic. The researcher presents this research by describing the cases then analyzing the case with the relevant concepts and references. After that, researchers draw conclusions based on the results of the analysis based on observations and searches of various sources. This study found that there was communication noise in the Covid-19 handling process in NTB. The noise is physical, technical, semantic, and psychological noise. Physical noise affects people with disabilities because they receive less attention. Technical noise affected the process of aid distribution and outreach of the Covid-19 outbreak. Semantic noise causes the public insight into the concepts used by the government. Psychological noise makes people not follow the government's appeal.Keyword: Noise, Communication, Covid-19[1] Universitas Mataram, Mataram, Indonesia, jamilnur@unram.ac.id[2] Universitas Muhammadiyah Surakarta, Surakarta, Indonesia, pra702@ums.ac.id[3] Universitas Mataram, Mataram, Indonesia, b.vira.safitri@gmail.com